Mobile phone appropriation of students and staff at an institution of higher learning - Abdul Karim, Nor Shariza; Oyebisi, Ishaq Oyefolahan; Mahmud, Murni (Emerald, 2010)
Purpose – The purpose of this paper is to investigate the adoption and appropriation of mobile phone (MP) technologies by building on the technology appropriation theories. The paper also looks into the choice of MP use through various attractors, the purposes of MP use and the extent of use of various MP applications and features by the targeted users. This paper also explores the influences of age, gender, and occupation type on MP appropriation.